Improving position resolution of neutron detectors with ultra-thin B4C foils. (1st March 2022) - Duarte, N.F.V.; Marcos, J.S.; Antognini, A.; Klauser, C.; Felix, S.A.; Monteiro, C.M.B.; Amaro, F.D.
Abstract: A new technique for detection of slow neutrons with gaseous detectors using ultra-thin layers with 10 B atoms is presented. The reaction between a thermal neutron and a 10 B atom releases two secondary particles, namely a 7 Li ion and an alpha particle, which due to momentum conservation are emitted in opposite directions, along the same line (back to back). Current boron coated neutron detectors are equipped with 10 B films with thicknesses of several micrometers, deposited on very thick substrate plates. However, since the ranges of the 7 Li ion and the alpha particle are of few micrometeres in most materials, one of these particles is always lost in the 10 B layer or substrate. As such, these detectors lose the ability to reconstruct the reaction line of action and to precisely determine the neutron position, as only one of the two secondary particles tracks can be measured. With the technique now presented, the sum of the 10 B layer and the substrate thicknesses is small enough to allow for both secondary particles to escape and ionize the gas in opposite sides of the 10 B converter foil. Independent readout structures, one on each side of the 10 B converter foil, detect each secondary particle and determine its track centroid and the deposited energy. Since the two secondary particles are emitted back to back, the neutron position can be obtained by combining the information recorded by the two readout structures. Through GEANT4 simulations, we verified that the spatial resolution can be significantly improved: our results show that, by using a B4 C layer with a thickness of 1 μm on a 0.9 μm Mylar substrate, the spatial resolution can by improved by a factor of eight, compared to conventional detectors with thick 10 B detection layers.